Efficacy of a respiratory physiotherapy intervention for intubated and mechanically ventilated adults with community acquired pneumonia: a systematic review protocol - van der Lee, L.; Hill, Anne-Marie; Patman, S. (University of Adelaide * Faculty of Health Sciences, 2017)
Review objectives: The objective of the review is to map evidence on the efficacy of a respiratory physiotherapy intervention for intubated and mechanically ventilated adults with community acquired pneumonia (CAP). Specifically, the review seeks to investigate if respiratory physiotherapy interventions can achieve the following for intubated and mechanically ventilated adults with CAP.